The opportunities and risks of mobile phones for refugees' experience: A scoping review. - Tiziana Mancini; Federica Sibilla; Dimitris Argiropoulos; Michele Rossi; Marina Everri (PLoS ONE)
Although mobile phones (MPs) are inexorably changing the forced migration experience, the realm of digital migration studies is still fragmented and lacking an analytical focus. Many research areas are still unexplored, while no narrative, scoping or systematic reviews have been conducted on this topic to date. The present review analyzed scientific contributions in Humanistic and Social Sciences with the aim to provide an overview of existing studies on the role of mobile phones (MPs) on refugees' experience, and to inform practice and policymaking for advancing the use of MPs for the protection of migrants' human rights. A scoping review was conducted using the Arksey and O'Malley framework and the JBI Reviewer's Manual recommendations. A three-step search was carried out in four bibliographic databases by three independent reviewers. Review selection and extraction were performed using an interactive team approach. Forty-three theoretical and empirical contributions were selected, and their content analyzed. The contributions ranged from 2013 to 2018 and varied in terms of disciplines, objectives, methodology, contexts, and migrants' origin, with the most studied group being Syrians. Five different topics concerning refugees' experience and MPs' usage emerged: (a) media practices in refugees' everyday lives; (b) opportunity and risks of MPs during the migration journey; (c) the role of MPs in maintaining and developing social relations; (d) potential of MPs for refugees" self-assertion and self-empowerment; (e) MPs for refugees' health and education. The results showed that modern devices, such as mobile phones, bring both risks and opportunities for refugees' experience, thereby both favouring and threatening asylum seekers' and refugees' human rights. Recommendations to policymaking and services and associations for advancing the use of MPs for the protection of the rights of migrants have been proposed.